Neurosurgical performance between experts and trainees: Evidence from drilling task. Issue 5 (23rd July 2021) - Chainey, Jonathan; O'Kelly, Cian J.; Kim, Michael J.; Zheng, Bin
Abstract: Background: Lumbar laminectomy is a common neurosurgery that requires precise manipulation of power drills. We examined the fine movement controls of novice neurosurgeons in drilling tasks and compared its accuracy to expert surgeons' performance. Methods: Four experts and three novice neurosurgeons performed a lumbar laminectomy on a three‐dimensional printed spine model. Scene video and surgeons' eye movements were recorded. Independent sample t ‐Tests were conducted on the number of jump, total fixation durations, pre‐jump fixation durations, post‐jump fixation durations and jump distances over novice and expert surgeons. Results: No statistically significant differences were recorded in terms of total fixations and pre‐jump fixation durations. However, novices had more jumping events, greater jump distances and longer post‐jump fixation durations when compared to expert neurosurgeons. Conclusion: Differences in movement accuracy and eye measures were found between expert and novice neurosurgeons during a simulated microscopic lumbar laminectomy. A more comprehensive understanding of surgeon's fine movement control mechanism and eye–hand coordination in microsurgery is essential for us before building an enhanced training protocol for surgical residents in neurosurgery.